2001
DOI: 10.1002/dev.1041
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated nervous system development contributes to behavioral efficiency in the laboratory mouse: A behavioral review and theoretical proposal

Abstract: The emergence of the laboratory mouse as a favored species for genetic research has posed a number of problems for scientists interested in the reflection of genetic influences in mouse behavior. It is commonly thought that rat behavior, which has been studied more extensively than mouse behavior, could be easily generalized to mice. In this article, a number of categories of behavior displayed by the mouse (motor, spatial, defensive, social) are reviewed and contrasted with the same categories of behavior dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 118 publications
2
78
0
Order By: Relevance
“…For example, mice are exclusively terrestrial while rats are also arboreal and aquatic (54,55). Rats also show superior performance across a broader array of spatial learning tasks, exhibit better spatial learning retention, and are more adept at using flexible spatial strategies to solve problems (56)(57)(58)(59)(60). One intriguing hypothesis is that axonal translation in the adult rat hippocampus supports the formation and experiencedependent modification of broad territory maps required to navigate larger and more varied habitats.…”
Section: Fxgs In the Adult Brainmentioning
confidence: 99%
“…For example, mice are exclusively terrestrial while rats are also arboreal and aquatic (54,55). Rats also show superior performance across a broader array of spatial learning tasks, exhibit better spatial learning retention, and are more adept at using flexible spatial strategies to solve problems (56)(57)(58)(59)(60). One intriguing hypothesis is that axonal translation in the adult rat hippocampus supports the formation and experiencedependent modification of broad territory maps required to navigate larger and more varied habitats.…”
Section: Fxgs In the Adult Brainmentioning
confidence: 99%
“…In contrast with Paul et al (2007), who found in the rat a second peak of activation at 5 min after fear conditioning, even higher than the one at 60 min, we could not find any evidence for this second peak of phospho-activated labeled cells in the mouse (Figure 2b). As reviewed in Whishaw et al (2001), several comparative studies already described anatomical and behavioral differences between the mouse and the rat in their performance in various behavioral tests. Therefore, researchers have an increasing awareness that these differences may complicate and limit the use of rat studies to interpret findings in mice (Asan et al, 2005;Jardim et al, 1999).…”
Section: The Time Course Of Erk/mapk Activation In the La Of The Mousmentioning
confidence: 99%
“…When the targeted gene is expressed in the brain, the behavioral phenotype of the genetically-manipulated mice may reveal genetic mechanisms underlying behaviors. Mice are a relatively social species [25,37,63]. Suitable mouse models for autism would show some relationship to the types of social deficits that are considered core symptoms of autism, including very low levels of eusocial behaviors and deficits in maintaining peer relationships [23,41].…”
Section: Introductionmentioning
confidence: 99%